The Digital Literacy and Students' Analytical Abilities: Challenges and Solutions in the Implementation of Technology Based Learning - Marselina, Suci; Rukmini, Ai; Judijanto, Loso; Nurlaila, Lela; Apriliyani, Eka Suci (The Future of Education Journal, 2025)
This study aims to analyze the relationship between digital literacy and students' analytical abilities in the context of technology-based learning, as well as to identify the challenges and solutions in its implementation. Digital literacy, which includes technical skills and the critical ability to access and evaluate information, is believed to influence how students think and solve problems analytically. The method used in this research is a literature review with a qualitative approach, where the author collects and analyzes various journals, articles, and previous studies related to digital literacy and technology-based education. The results show that although high digital literacy can enhance students' analytical abilities, there are several key challenges faced, including the digital access gap, the unpreparedness of most teachers to integrate technology into learning, and the lack of students' understanding of the importance of critical thinking. Additionally, the proposed solutions include increasing teacher training, developing curricula that integrate digital literacy, and using problem-based learning (PBL) models that can facilitate the improvement of students' analytical abilities. The conclusion of this study is that to maximize the potential of technology-based learning, a holistic approach is needed, involving strengthening students' digital literacy, improving teacher readiness, and providing more equitable access to technology.